AI-SUPPORTED EFL WRITING INSTRUCTION: A STUDY ON THE USE OF CHATGPT - Moh. Thohir Wijaya; Dwita Laksmita Rachmawati (University of Kuningan, 2026)
The integration of artificial intelligence (AI) into language education presents innovative opportunities for enhancing English as a Foreign Language (EFL) writing instruction. This mixed-methods study investigated the use of ChatGPT as an AI-powered digital writing assistant to improve EFL learners' writing skills, specifically examining its impact on idea development, grammatical accuracy, vocabulary use, and overall text organization. A total of 60 EFL university students (n=60) participated in AI-assisted writing activities over a six-week intervention period. Quantitative data were collected through pre- and post-writing tests, while qualitative data were gathered from student reflective journals and open-ended questionnaires. Results from paired-samples t-tests revealed a statistically significant improvement in overall writing scores (t(59) = 6.42, p < .001), with a mean increase of 15.8% and a large effect size (Cohen's d = 0.83). Improvements were particularly notable in coherence, lexical diversity, and grammatical accuracy. Thematic analysis of reflective journals identified two salient themes: (1) reduced writing anxiety, as students reported feeling less apprehensive about making errors when supported by AI-generated feedback, and (2) enhanced idea generation, with learners noting that ChatGPT facilitated brainstorming and improved content elaboration. Students also reported higher levels of motivation and self-confidence when engaging with AI-based support. Despite these benefits, challenges including unequal access to technology, potential over-reliance on AI tools, and the need for critical evaluation of AI-generated content were identified. The study concludes that ChatGPT can serve as an effective supplementary tool in EFL writing instruction when integrated judiciously, with pedagogical guidance remaining essential to ensure that AI use supports, rather than replaces, the development of learners' independent writing competence.